Pemenuhan Hak Santri atas Kasus Pelanggaran Hak Asasi Manusia oleh Oknum Pondok Pesantren - Suci Amelia Harlen (Badan Strategi Kebijakan Hukum, 2022)
Sexual violence is one of the human rights violations in which women are the dominant victims. To date, most victims who have experienced violence are reluctant to submit complains because they do not know that the situation that happened to them was violence and because of the lack of support from their families. The female students who became the victims had been lured by their ideals, lied to for religious reasons, and were verbally threatened by HW. The focus of this research is to analyze what kind of human rights violations that were committed by the leaders of Islamic boarding schools against female students. The research method uses empirical juridical because it examines the situation happened what is happening in society. This study aims to provide solutions to violations against human rights that have occurred and as anticipation so that similar human rights violations do not occur. The results of the study show that sexual violence can be prevented by providing sexual understanding to children, providing complaint services, and having parental control over children. However, if sexual violence has occurred, then the state needs to help in providing access to education and access to health for victims, as well as punish the perpetrators.